Study Of Soil Physical Properties In Ex-Gold Mining Land, Oil Palm (Elaeis Guineensis Jacq.) Plantation, And Forests On Ultisol - Resti Arjuni Santi; Dewi Rezki; Adrinal (Jurusan Budidaya Perkebunan, 2022)
The soil physical properties are one of the components of soil fertility that function as a place for roots to penetrate. Different types of land uses affect the soil physical properties, especially on the availability of water and soil aeration which indirectly affects the availability of nutrients in the soil. Research on the soil physical properties of ex-gold mining, oil palm plantations and forests was carried out on Ultisol located in Tebing Tinggi Village, Dharmasraya Regency from April until October 2021. The objective of this study was to obtain the comparison of soil physics properties in ex-gold mining land with oil palm and forest land on Ultisol. The method on this study was a survey with purposive sampling on three different land uses (ex- gold mining land, oil palm land and forest) at a depth of 0-20 cm and 20-40 cm and it was replicated 3 times. The observed parameters were soil texture, organic matter, volume weight, soil pore space, soil water content, permeability, and soil aggregate stability. Based on soil analysis in the laboratory, it was obtained that the physical conditions of the soil in three different land uses, i.e the physical condition of the oil palm land and forest were better than the ex-gold mining land. The soil texture on ex-gold mining land was classified on sandy clay loam and sandy loam with a very low organic matter content (0,20-1,72 %) if compared with oil palm and forest land. The volume weight in each land use was relatively high with the total soil pore space was low except in oil palm land depths of 0-20 cm, which is 69,93 % vol (moderate). Permeability was slow to moderate with the soil aggregate stability classified as unstable to steady. Soil water content was relatively low except in forest land depths of 20-40 cm which very high criteria (33,93 %).